THE TRAPS OF IDENTIFICATION - S.N. YAREMENKO (Advanced Engineering Research)
The article analyses the process of identification as person's choice of life sensible schemes. Senses and styles of life are represented as key identificative personal characteristics. Special attention is paid to identificative traps what are very actual especially in the society of risks.